Risk of Hearing Loss After Bacterial Meningitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Presence of sensorineural hearing loss (>25 dB) was determined in 628 school-aged children born between 1986 and 1994 and survived non-Hemophilus influenzae type B (HiB) bacterial meningitis between 1990 and 1995 in a study at VU Medical Center, Amsterdam; and University Medical Center and Wilhelmina Children's Hospital, Utrecht, the Netherlands.